Shaping Language: Key Factors Behind Linguistic Shift - Agustina, Stefany; Yulianto, Andrias (Universitas Stikubank (UNISBANK) Semarang, 2025)
Living in a multicultural and multilingual society, on one hand, provides individuals with opportunities to expand their social network, enhance cultural understanding and adopt new language. However, on the other hand, this can lead to language shift, interchangeably called language change, in which individuals gradually abandon their mother tongue in favor of a more dominant language. This paper investigates the phenomenon of language change in the 2004 movie entitled “Spanglish” The research employs qualitative research design, describing the dialog based on the movie. It is expected that this research can contribute to develop an understanding of the dynamic nature of language, and to the educators and researcher for further research. Keywords: Language change, factors influencing, multicultural, Multilingual, Spanglish, Language shift.